Hyperammonemic encephalopathy during XELOX regimen. Is it capecitabine or oxaliplatin responsible?. Issue 10 (November 2020) - Di Federico, Alessandro; Nuvola, Giacomo; Sisi, Monia; Lenzi, Barbara; Nobili, Elisabetta; Campana, Davide
Abstract : Hyperammonemic encephalopathy represents a rare adverse effect of several chemotherapeutic agents, occurring in about 0.7% of patients treated with fluoropyrimidines, and it is independent from dihydropyrimidine dehydrogenase deficiency. Instead, its physiopathology is linked to the inhibition of Krebs cycle by fluoroacetate, leading to decreased ATP production, and to the inhibition of the urea cycle. Oxaliplatin seems to induce hyperammonemic encephalopathy in a similar way, acting on mitochondria. Here, we report the intriguing case of acute hyperammonemic encephalopathy in a 65-year-old patient with preserved liver function, who was treated with oxaliplatin and capecitabine for a metastatic, G1, atypical lung carcinoid. We reviewed the literature and found very few reports of oxaliplatin or capecitabine-induced hyperammonemic encephalopathy. Out of five cases of capecitabine-related hyperammonemic encephalopathy analyzed (four plus our case), median time to hyperammonemic encephalopathy onset was 6 days, with median serum ammonia levels of 213 μmol/L. Oxaliplatin-related hyperammonemic encephalopathy analyzed cases were three (two plus ours), with a median time to hyperammonemic encephalopathy of 11 days and median serum ammonia levels of 167 μmol/L. Identified predisposing factors for chemotherapy-induced hyperammonemia, such as dehydration, liver and renal impairment, infections, and sarcopenia were absent in our case. We hypothesize that the combination of a platinum-derivative and a fluoropyrimidine multiplies the risk of hyperammonemic encephalopathy, even in the absence of predisposing factors nor impaired liver function. We therefore suggest to always consider the risk of hyperammonemia when starting fluoropyrimidines-based chemotherapy, especially combined with platinum-derivatives, and to timely investigate neurologic symptoms monitoring ammonia serum levels.